Manfaat ramuan virgin coconut oil (VCO) dan kunyit (Curcuma longa) untuk kesehatan kulit wajah: Advantages of virgin coconut oil (VCO) and turmeric (Curcuma longa) for skin health - Putri, Putu Ayu Cempaka; Cahyaningrum, Putu Lakustini (Universitas Hindu Indonesia (UNHI) Press, 2024)
Beauty is very important for every woman. Looking beautiful can cause women to feel confident in every activity they do. The emergence of skin problems can reduce the self-confidence of adolescents and young adults due to reduced facial beauty. Efforts to maintain healthy skin can be done by utilizing natural ingredients including virgin coconut oil (VCO) and turmeric (Curcuma longa). This research was conducted in Denpasar City. Where the people of Denpasar City who are heterogeneous and live in urban areas, experience many complaints about the health of their facial skin. This study aims to determine the use of turmeric concoctions and pure coconut oil as natural ingredients that can clean and maintain facial skin health. This research is qualitative research using ethnomedicine theory and structural functionalism. Data collection methods used in this research are library research, observation, and interviews. The sampling technique used purposive sampling technique. Based on the research results, it is known that the ingredients of virgin coconut oil (VCO) and turmeric (Curcuma longa) can maintain facial skin health because they are made from natural ingredients and are easy to obtain and the price is affordable because they are materials commonly used by the community. The procedure for using the ingredients of virgin coconut oil (VCO) and turmeric (Curcuma longa) is in certain way and is done at least once a day. As well as the implications of using virgin coconut oil (VCO) and turmeric (Curcuma longa) ingredients for facial skin health is that facial skin becomes more moisturized, reduces dullness, overcomes acne, protects facial skin from microbes, and reduces wrinkles.